OPEC Fund and development cooperation in a changing world : selected statements... - Abdulai, Y. Seyyid (OPEC ViennaAT, 2003)
Outlines the projects and programmes of the OPEC Fund, the interventions and contributions of the institution to global development thinking and processes and the policy choices and instruments at the disposal of the Fund. Reveals the positions of OPEC member countries on many vital issues of our day, reflecting viewpoints, and oftentimes, adjustments and accommodation that have had to be made to adapt to changing circumstances.